Religious Harmony in East Nusa Tenggara: Insights into Local Tradition and Values of Muslim Communities - Arif, Mahmud; Sabarudin, Sabarudin; Kurjum, Mohammad; Abdullah, Rafidah binti (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
Kupang City, located in East Nusa Tenggara (NTT) province, stands out for its notable success in fostering tolerance among religious communities. Its significance lies in (a) being the largest city in NTT, (b) having a longstanding history of Islamic development, and (c) the proclamation of local leaders demonstrating a firm commitment to preserving Kupang as an exemplar of religious harmony. In light of these aspects, the authors conducted qualitative field research on Muslim village communities in Kupang to explore how harmony is maintained among religious groups. This research is based on the theoretical assumption that understanding the world requires a native point of approach, relying on the researcher's perspective. The findings reveal that a crucial foundation for harmony among religious communities is the residents' highly tolerant attitude, reflecting the active tolerance embedded in local wisdom. This local wisdom is further reinforced by the recognition of diversity as a defining feature of Kupang City's identity. The actualization of this value is evident in religious and cultural traditions, exemplified by the Siripuan tradition in Airmata Village. The dynamic nature of harmony among religious communities is underscored, with one contributing factor being the lower positive feelings experienced by minorities compared to the majority. Addressing this discrepancy is crucial for anticipating and mitigating potential challenges among Muslim minorities.